Singapore's Export Elasticities : A Disaggregated Look into the Role of Global Value Chains and Economic Complexity - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper ;, 2016)
Singapore is one of the world's most open economies, with the size of its trade reaching about 350 percent of its GDP. With the rise of highly diversified cross-border production networks, Singapore has come to play an integral role in the global supply chain with heavy reliance on foreign contents in its exports and production. It has also successfully moved up the value chain, exporting goods with high sophistication and economic complexity. Against this backdrop, in this paper, using disaggregate industry/product level trade data, we revisit Singapore's export elasticities and find that growing participation in global production chains and rising export complexity are important determinants.